Somatostatinoma Presented as Double-Duct Sign - Zakaria, Ali (Case Rep Gastrointest Med, 2019)
Somatostatinoma is a rare neuroendocrine tumor with an incidence rate of 1 in 40 million people. It presents mostly as asymptomatic tumor diagnosed incidentally on imaging or surgery when evaluating or treating possible causes of abdominal pain. It also can present with vague symptoms, or as a clinical triad of glucose intolerance, steatorrhea, and achlorhydria. The majority of somatostatinomas are present in the pancreatic head, followed by the duodenum, the pancreatic tail, and rarely the ampulla of Vater. The prognosis is poor as more than 77% of cases present as advanced disease with local invasion or distant metastasis. Surgical resection is the main treatment for early stage disease. Other treatment options include somatostatin analogue, molecular targeted therapy, and cytotoxic chemotherapy. The scarcity of somatostatinoma cases led to the lack of fully formulated treatment options. Herein, we present a 43-year old male patient who was referred by his primary care physician to our gastroenterology clinic due to elevated liver function test and double-duct sign on CT scan. We performed an ERCP, which revealed 2 cm ampullary lesion with upstream obstruction. Biopsies were taken and histopathology was unrevealing. He underwent a laparoscopic pancreaticoduodenectomy with histopathology revealed stage IIb somatostatinoma. Treating physicians should hold a high index of suspicion and maintain a broad differential diagnosis of elevated liver enzymes.